The influence of environmental regulation on high-quality development of marine economy from different subjects’ perspectives - Wu, Fan; Cui, Fengxiang; Liu, Tao (Frontiers in Marine Science, 2023)
As the high-quality development of marine economy cannot be separated from the improvement of marine ecological environment quality, it is of great importance to clarify the relationship between environmental regulation and the high-quality development of marine economy. In this paper, firstly, an aggregative indicator system of high-quality development of marine economy was constructed to dynamically describe and analyze the overall and provincial trends of high-quality development indicators of marine economy from two dimensions: time trend and spatial pattern. Then, a theoretical analysis framework of environmental regulation affecting the high-quality development of marine economy was constructed, and the theoretical explanation and hypotheses were put forward and tested from the action mechanism of different types of environmental regulation affecting the high-quality development of marine economy, such as command control, market incentive and public participation. At last, the paths and countermeasures of environmental regulation to promote the high-quality development of marine economy were put forward combined with the theoretical analysis and empirical test results.